KEPASTIAN HUKUM PRINSIP PEMILIK MANFAAT (BENEFICIAL OWNERSHIP) SERTA PERANAN NOTARIS BERDASARKAN PERMENKUMHAM NOMOR 15 TAHUN 2019 - Razi, Fatrul; Rembrandt, Rembrandt; Mannas, Yussy Adelina (UNES Law Review, 2023)
Notaries as public officials have an obligation to apply the principle of recognizing beneficial owners in a corporation where this obligation is not regulated in UUJN. On the one hand, a notary does play an important role in disclosing beneficial ownership of a corporation, but on the other hand, the transparency of beneficial ownership disclosure must be based on honest and clear information from parties representing the corporation. This is due to the existence of beneficial ownership which cannot be fully detected by a notary. The problems are what are the legal consequences if the principle of recognizing beneficial owners (BO) is not implemented and what is the urgency of applying the principle of recognizing beneficial owners (BO) in carrying out notary duties. This legal research uses normative legal research, namely library research, which is a data collection method by studying books, laws and regulations, and writings related to this research. While the nature of the research is analytical descriptive, that is, it gives a clear and detailed description of an event that occurred. The results of research on legal consequences if the principle of recognizing beneficial owners (BO) is not implemented are given administrative sanctions, namely revoking the notary's license if violations are found, supervision in the implementation of the application of the BO principle is carried out by the Minister of Law and Human Rights through the Director General of General Legal Administration. Meanwhile, the notary's responsibility for the deed he made is that in civil terms the notary is only responsible for the head of the deed, meaning that it contains the authority of the appearers in signing the deed, then for the closing deed which contains the authority of the witnesses then the appearers are confronted with signing the deed, whereas against contents of the deed the notary is only responsible that the deed he made does not violate the clauses prohibited by law and the provisions stipulated in Article 1320 of the Civil Code. Criminally, a notary can be prosecuted in court if at a later date, the competent authorities can prove that the notary has consciously entered information that benefits one party and harms the other party. And the urgency of applying the principle of recognizing beneficial owners (BO) in carrying out notary duties is that basically the obligation to disclose beneficial ownership is carried out by parties who wish to use the services of a notary. The role and position of a notary is as a supporting system in disclosing beneficial ownership of a corporation, namely in this case during the process of inputting data related to the establishment or changes to the corporate statutes/bylaws. Thus the obligation related to disclosure of beneficial ownership cannot be borne by the notary but the service user.